Silicon oxide buffer layer at the p–i interface in amorphous and microcrystalline silicon solar cells - Bugnon, Grégory; Parascandolo, Gaetano; Hänni, Simon; Stuckelberger, Michael; Charrière, Mathieu; Despeisse, Matthieu; Meillaud, Fanny; Ballif, Christophe (Solar energy materials and solar cells, 2014)
The use of intrinsic silicon oxide as a buffer layer at the p–i interface of thin-film silicon solar cells is shown to provide significant advantages. For microcrystalline silicon solar cells, when associated with highly crystalline i-layers deposited at high rates, all electrical parameters are improved. Larger efficiency gains are achieved with substrates of increased roughness. For cells with an improved i-layer material quality, there is mainly a gain in short-circuit current density. An improvement in carrier collection in the blue region of the spectrum is systematically observed on all the cells. The presence of a silicon oxide buffer layer also promotes the nucleation of the subsequent intrinsic microcrystalline silicon layer. In amorphous silicon solar cells, the silicon oxide buffer layer is proven to act as an efficient barrier to boron cross-contamination, eliminating the need for additional processing steps (e.g. water vapor flush), while providing a wide bandgap material at the interface. The implementation of silicon oxide buffer layers for both types of cells thus provides a decisive improvement, as it allows extremely fast deposition of the full p–i–n stack of layers of the cell in a single-chamber configuration while providing a high-quality substrate-resilient p–i interface. [Display omitted] •We implemented SiOx buffers at the p/i interface of thin film silicon solar cells.•µc-Si:H solar cells show superior performances leading to record cells.•Enhanced anti-reflective effect and nucleation of i-(µc-Si:H) layer are observed.•a-Si:H solar cells with SiOx buffer have better stabilized efficiencies.•Effective way to reduce boron cross-contamination in single chamber process.